INGATAN SEBAGAI DASAR PRAKTIK AKUNTANSI PERTANIAN - Hidayati, Annisa; Umairoh, Elvin; Windayani, Erilla; Alfathu Rizqi, Farhan; Hudzaifah; Andriany Agus Tianingrum, Putri; Anggraini, Reza; Zhorif Abhinawa, Rozan (Forum Dosen Ekonomi dan Bisnis Islam (FORDEBI), 2023)
The purpose of this study was to understand accounting practices and processes in farming activities in Karangrejo Village, Malang Regency. Data analysis used descriptive qualitative with five informants as actors of farming activities. The results showed that memory accounting practices were carried out in every part of the agricultural cycle which included pre-planting, planting, harvesting and post-harvest processes. Recording is standard and only relies on farmers' memories regarding capital, harvest yields, and is based on mutual trust and mutual sincerity. The basis of belief and sincerity is the basis for Islamic values (faith) to be carried out in daily farming. Consequently, memory accounting is not profit-oriented but for the common good. Abstrak Tujuan penelitian ini adalah untuk memahami praktik dan proses akuntansi dalam aktivitas bertani di Desa Karangrejo, Kabupaten Malang. Analisis data yang digunakan deskriptif kualitatif dengan lima orang informan sebagi pelaku aktivitas bertani. Hasil penelitian menunjukkan bahwa praktik akuntansi ingatan dilakukan dalam setiap bagian siklus pertanian yang meliputi proses pra tanam, tanam, panen, dan pasca panen. Pencatatan baku dan hanya mengandalkan ingatan para petani terkait modal, hasil panen, serta berdasarkan sikap saling percaya dan saling ikhlas. Dasar kepercayaan dan keikhlasan menjadi dasar nilai-nilai (keimanan) Islam dijalankan dalam keseharian bertani. Konsekuensinya akuntansi ingatan tidak berorientasi pada laba melainkan kesejahteraan bersama.